Pembuatan Sabun Cair Berbasis Minyak Kelapa Dengan Proses Saponifikasi Untuk Menghambat Pertumbuhan Bakteri Dengan Penambahan Minyak Zaitun (Pure Olive Oil) Untuk Pelembap Kulit - Syamsul Bakhri; Amirullah Amirullah; Muhammad Ridha Kasim (Agricultural Faculty, 2022)
This research was conducted to produce and determine liquid soap products that function as skin moisturizers and can inhibit microbial growth. In the process of making this liquid soap, two formulas are used, namely formula 1 which is made from coconut oil and alkali of KOH with the addition of olive oil and formula 2 which is made from coconut oil and alkali of KOH without the addition of olive oil . The manufacture of liquid soap in this study was carried out experimentally using the hot process method. Organoleptic testing with parameters of foam, skin dryness, and skin moisture was carried out using analytical observational and questionnaire methods involving fifteen correspondents. Testing the inhibition of microbial growth using Staphylococcus aureus bacteria contamination. The results obtained from this research are liquid soap formula 1 and formula 2 have a lot of foam and a very strong microbial growth retardant power, liquid soap formula 1 can moisturize the skin, and liquid soap formula 2 dries the skin. The results of this research, God willing, will be a reference for the author to continue this research to the stage of perfection and it is hoped that the results of this research can also be useful for the ummah and the nation in realizing a healthy life .